Kandungan Bahan Kering Silase Pakan Komplit Berbasis Azolla Pinnata dengan Lama Fermentasi Berbeda: Dry Material Content of Complete Feed Silage on Azolla Pinnata B Based on Different Fermentation Times - Nurwahidah Jamaluddin; Ulva Dianasari; Fadliah M; Andi Waliana Syaggaf; Budi Wardiman; Muhammad Arsan Jamili (Universitas Islam Negeri Alauddin Makassar, 2022)
Azolla plants that have a high water content affect the fermentation results. This study aims to study the changes in the nutritional value of dry matter silage of complete feed based on azolla with different fermentation times. This research was conducted using a completely randomized design (CRD) consisting of 3 treatments and 5 replications. The treatments consisted of: RO: Fermentation 0 days (Control), R1: Fermentation 14 days And R2: Fermentation 28 days. Where the variable being measured is the value of dry matter (BK). The data were analyzed using analysis of variance and continued with Duncan's test for the real difference test. The value shows that the dry matter value in the R0 treatment was significantly different (P<0.05) with the R2 treatment with R1, and in the R1 treatment it was not significantly different (P>0.05) with the R2 treatment.